(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study assessment of adequacy of office technology and management curriculum relative to employment requirements in North-West Nigeria was necessitated by the need to ensure that the products perform satisfactorily in employment. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. Ex-post facto and survey research design were used forthe study. Population of 456 principal officers of public and private establishments in North-West Nigeria wasstudied without sampling. Forty Nine questionnaire items relating to adequacy of contents of Information and Communication Technology and records management course units were developed and validated by panel of experts. The internal consistency reliability co-efficient of the instrument was established using Pearson Product Moment Correlation Co-efficient and the overall reliability of the instrument was established using K.R-20 formula. The internal consistency reliability coefficient obtained were 0.97 and 0.95respectively for the two clusters with the overall reliability co-efficient of 0.96. Mean and standard deviation were used to analyze data in relation to the research questions while ztest was used to test the null hypotheses. The findingsrevealed that Office Technology and Management curriculum was adequate forICT and records management content for employability skills acquisition of the graduates. Furthermore, the respondents differed significantly in their mean ratings of adequacy of OTM curriculum on ICT and records management. Based on the above findings it is recommended among others that employers of labour, particularly Federal and States Department of Establishment and Training/Offices of Head of Service and Representatives of private establishmentsshould be co-opted in the future reviewof OTM curriculum.